Bio-lignin modified nitrile rubber, high-damping and oil-resistant efficient shock-absorbing rubber pad for compressor and preparation method of bio-lignin modified nitrile rubber and oil-resistant efficient shock-absorbing rubber pad
By introducing bio-based lignin branches into nitrile rubber, and utilizing the macromolecular active groups and hydrogen bonding of lignin, the problems of insufficient damping performance and liquid resistance of nitrile rubber are solved, achieving a high-damping and oil-resistant high-efficiency shock absorption effect, suitable for high-damping and oil-resistant rubber pads.
Patent Information
- Application Number
- CN202511267443.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2025-11-07
AI Technical Summary
In the existing technology, the damping performance and liquid resistance of nitrile rubber have not been effectively improved, especially in terms of high damping and oil resistance.
By introducing bio-based lignin branches into nitrile rubber, the friction between molecular chains is increased by utilizing the macromolecular active groups and hydrogen bonding of lignin, thereby improving its damping and liquid resistance properties. Specific methods include grafting terminal thiol lignin onto nitrile rubber and modifying it through the Thiol-ene reaction.
It significantly improves the damping and liquid resistance of nitrile rubber, making it suitable for high-damping and oil-resistant high-efficiency shock-absorbing rubber pads, especially showing excellent shock absorption in compressor applications.
Smart Images

Figure BDA0005583681640000091 
Figure HDA0005583681650000011 
Figure HDA0005583681650000021
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of rubber pads, in particular to a bio-based lignin modified nitrile rubber and a high-damping, oil-resistant, high-efficiency shock-absorbing rubber pad for compressors, and a preparation method thereof. The rubber pad has excellent damping and liquid resistance. BACKGROUND
[0002] Damping material, also known as vibration attenuation material, rubber is an ideal sealing material and damping material. Since rubber is a viscoelastic material, under the action of external force (especially alternating stress), the molecules overcome the internal friction resistance between the chain segments, and the resulting hysteresis loss and heat generation are a manifestation of damping performance. Currently, DMA is mainly used to evaluate the damping performance of materials. The higher the tan delta under the relevant temperature, the better the damping performance. In academia, the area under the tan delta curve is usually used to judge the advantages and disadvantages of damping materials.
[0003] Currently, flexible and rigid rubber is used as the main raw material for damping products, such as styrene-butadiene rubber and nitrile rubber, which have benzene rings and cyano groups on the side chains, respectively, and steric hindrance effects can increase damping effects. Butyl rubber has two methyl side chains on each repeating unit, which increases the internal rotation barrier. Nitrile rubber is the preferred rubber for liquid-resistant damping materials due to its dual properties of damping and liquid resistance.
[0004] Patent No. CN 112094463A reports a damping rubber using butyl rubber and chlorosulfonated polyethylene. Patent No. CN 112175340 A reports a damping material composed of a blend of styrene-isoprene block copolymer and butyl rubber. Patent No. CN 113896859A introduces a bio-based polyurethane damping material. Currently, there is no patent that grafts bio-based lignin onto nitrile rubber to improve the damping performance and liquid resistance of nitrile rubber. SUMMARY
[0005] Therefore, the present application aims to provide a bio-based lignin modified nitrile rubber and a high-damping, oil-resistant, high-efficiency shock-absorbing rubber pad for compressors, and a preparation method thereof. The rubber pad has excellent damping and liquid resistance.
[0006] The present application provides a bio-based lignin modified nitrile rubber, which is prepared by grafting nitrile rubber with terminal mercaptan lignin.
[0007] The terminal mercaptan lignin is prepared by modifying bio-based lignin with 3-mercaptopropionic acid, and the bio-based lignin is selected from one or more of alkali lignin, dealkali lignin, sodium lignosulfonate, and calcium lignosulfonate.
[0008] The application provides a preparation method of the lignin grafted butyl nitrile rubber.
[0009] The butyl nitrile rubber, the mercapto lignin and a photoinitiator are mixed, tabletted, and reacted under ultraviolet irradiation to obtain the lignin grafted butyl nitrile rubber.
[0010] Preferably, the ultraviolet irradiation adopts a wavelength of 365 nm, a power of 110-130 W, and an irradiation time of 170-190 min.
[0011] Preferably, the photoinitiator is selected from one or more of 2,2-dimethoxy-2-phenylacetophenone, benzil ketone, 2,2'-bis(trifluoromethyl)phenyl phosphate, 2,4,6-trimethylphenyl phosphate, 2,2'-bis(p-hydroxyphenyl)propane and 2,2'-bis(p-methoxyphenyl)propane.
[0012] Preferably, the terminal mercapto lignin is prepared by the following method:
[0013] After the lignin is dehydrated, the dehydrated lignin is mixed with dehydrated DMSO, an esterification condensing agent is added, the 3-mercaptopropionic acid DMSO solution is added dropwise after the esterification condensing agent is completely dissolved, and the reflux reaction is carried out under a nitrogen atmosphere to obtain the terminal mercapto lignin.
[0014] Preferably, the esterification condensing agent is selected from one or more of 4-N,N-dimethylpyridine, N,N'-dicyclohexyl carbodiimide, carbonyl diimidazole and sulfuryl chloride.
[0015] Preferably, the reflux reaction is carried out at a temperature of 65-75 DEG C for 70-75 h.
[0016] The application provides a high-damping and oil-resistant efficient shock-absorbing rubber pad for a compressor, which comprises the following components in mass parts:
[0017] The bio-based lignin modified butyl nitrile rubber is 100.0-150.0 parts, the carbon black is 50-70 parts, the zinc oxide is 2.0-5.0 parts, the stearic acid is 1.0-3.0 parts, the antioxidant is 1.0-6.0 parts, the accelerator is 0.5-5 parts, and the sulfur is 1.0-10.0 parts.
[0018] Preferably, the type of the carbon black is N330.
[0019] The accelerator is selected from one or more of accelerator NOBS, accelerator CZ, accelerator NS, accelerator DTDM, accelerator DM, accelerator M and accelerator TMTD.
[0020] The application provides a preparation method of the high-damping and oil-resistant efficient shock-absorbing rubber pad for a compressor.
[0021] Mixing, discharging, passing through the roller, and placing the sheet to obtain the masterbatch;
[0022] Mixing the masterbatch and the accelerator and sulfur, passing through the thin pass, and placing the sheet after vulcanization to obtain the high-efficiency shock-absorbing rubber pad.
[0023] The application provides a bio-based lignin modified nitrile rubber, which is prepared by grafting nitrile rubber with terminal mercapto lignin. BRIEF DESCRIPTION OF DRAWINGS
[0024] Figure 1 The infrared spectrum of the delignified lignin and mercapto lignin in Example 1 is shown in the figure.
[0025] Figure 2 The dynamic mechanical property figure of the rubber pad prepared in the examples and the comparative examples of the application is shown in the figure. DETAILED DESCRIPTION
[0026] The application provides a bio-based lignin modified nitrile rubber, which is prepared by grafting nitrile rubber with terminal mercapto lignin.
[0027] The terminal mercapto lignin is prepared by modifying bio-based lignin and 3-mercaptopropionic acid, and the bio-based lignin is selected from one or more of alkali lignin, delignified lignin, sodium lignosulfonate and calcium lignosulfonate.
[0028] The application grafts and modifies nitrile rubber by using bio-based lignin, improves the damping performance and liquid resistance of the nitrile rubber, and is used for high-end shock-absorbing, sealing and other products with high damping and high liquid resistance.
[0029] The bio-based lignin in the application is a natural complex organic polymer compound, which is widely present in plant cell walls and is an important component of plant structure and function; the bio-based lignin is low in price, widely distributed, pollution-free, renewable and degradable, and has a wide application prospect. The aromatic structure and rich active groups, such as hydroxyl groups, carbonyl groups and methoxyl groups, of the bio-based lignin can be used as active sites for reaction and grafting with rubber; the six-membered ring structure in the molecule, the intramolecular and intermolecular hydrogen bond structure increase the σ bond rotation barrier of C-C, and have strong damping and shock-absorbing effects.
[0030] The bio-based lignin grafted nitrile rubber in the application is prepared according to the following method:
[0031] The nitrile rubber, the terminal mercapto lignin and the initiator are mixed, tabletted, reacted under ultraviolet irradiation, and the bio-based lignin grafted nitrile rubber is obtained.
[0032] The application grafts the lignin onto the nitrile rubber through certain chemical reactions, can obviously increase the damping effect of the nitrile rubber, and improves the liquid resistance of the nitrile rubber.
[0033] In the application, the terminal mercapto lignin is prepared according to the following method:
[0034] The lignin is dissolved in dimethyl sulfoxide (DMSO) and mixed, the esterification condensing agent is added, after complete dissolution, the 3-mercaptopropionic acid acetone solution is added dropwise, and the reaction is carried out under refluxing in a nitrogen atmosphere, and the terminal mercapto lignin is obtained.
[0035] The application introduces the lignin into mercapto through esterification reaction, the Thiol-ene reaction occurs between the mercapto and the double bond of the nitrile rubber, the lignin is grafted onto the nitrile rubber, the damping and shock absorbing performance of the rubber compound is improved, and the liquid resistance of the rubber compound is obviously improved due to the strong polar structure of the lignin molecule.
[0036] In the application, the dimethyl sulfoxide is stirred with calcium hydride for 10-14 hours to remove water, and is distilled under reduced pressure for standby use.
[0037] In the application, the lignin is dehydrated under vacuum at 48-52 DEG C for 55-90 hours, preferably at 50 DEG C for 72 hours, and the dehydrated lignin is obtained.
[0038] In the application, the dehydrated lignin is placed in a three-necked flask after nitrogen replacement, the dehydrated DMSO is added, stirred, the esterification condensing agent is added, after the esterification condensing agent is completely dissolved, the 3-mercaptopropionic acid DMSO solution is added dropwise.
[0039] The esterification condensing agent used in the present application is selected from one or more of 4-N,N-dimethylpyridine (DMAP), N,N'-dicyclohexyl carbodiimide (DCC), carbonyl diimidazole (CDI) and sulfonyl chloride. The present application preferably uses a constant pressure dropping funnel to slowly drop the 3-mercaptopropionic acid solution in acetone. After the dropping is completed, the present application replaces the constant pressure dropping funnel with a condenser, protects with nitrogen, and refluxes; the temperature of the refluxing reaction is 65-75℃, and the time is 70-75h; in a specific embodiment, the temperature of the refluxing reaction is 70℃, and the time is 72h. After the refluxing reaction is completed, acetone is settled, suction filtration is performed, the filter cake is washed with acetone three times, vacuum drying is performed, and mercaptolignin is obtained. The temperature of the vacuum drying is 35-45℃, and the time is 22-26h; in a specific embodiment, the temperature of the vacuum drying is 40℃, and the time is 24h.
[0040] The butyl nitrile rubber in the present application is a synthetic rubber prepared by emulsion or solution polymerization of butadiene (Butadiene) and acrylonitrile (Acrylonitrile) two monomers. Its main components are acrylonitrile and butadiene, and the acrylonitrile content is usually between 15% and 53%. According to the different content of acrylonitrile, butyl nitrile rubber can be divided into low nitrile, medium nitrile, high nitrile and super high nitrile grades, and its brand includes but is not limited to NBR2808, NBR3304, NBR1906, NBR3305, NBR3308, NBR3307, NBR6250, NBR 6280, NBR7030, NBR 2875, N1945, N220S, N1704, NBR2707, NBR2604, NBR3606, N230S, N240S, etc.
[0041] The photoinitiator in the present application is selected from one or more of 2,2-dimethoxy-2-phenylacetophenone, benzoylformone (BPO), 2,2'-bis(trifluoromethyl)phenyl phosphate (BAPO), 2,4,6-trimethylphenyl phosphate (LAP), 2,2'-bis(p-hydroxyphenyl)propane (DHBP) and 2,2'-bis(p-methoxyphenyl)propane (MOP).
[0042] The torque rheometer is set to a temperature of 70 DEG C, and the butyl rubber is added and stirred at 68-72 rps for 58-63 s, then the thiol-terminated lignin and photoinitiator are added; the butyl rubber, thiol-terminated lignin and photoinitiator are stirred for 4.5-5.5 min to remove the glue, and the rubber sheet is pressed on an open mill with a roller temperature of 45-55 DEG C and a roller distance of 0.2 mm. The rubber sheet is placed in a nitrogen glove box, and reacts under the irradiation of a UV light source; the wavelength of the UV irradiation is 365 nm, the power is 110-130 W, and the irradiation time is 170-190 min; in a specific embodiment, the power is 120 W, and the irradiation time is 3 h. Thiol-ene reactions occur between them, and the thiol-terminated lignin is grafted onto the butyl rubber to produce lignin-grafted butyl rubber.
[0043] The application provides a high-damping and oil-resistant high-efficiency shock-absorbing rubber pad for a compressor, which comprises the following components in mass fractions:
[0044] The lignin-grafted butyl rubber (lignin-g-NBR) is 100.0-150.0 parts, the carbon black is 50-70 parts, the zinc oxide is 2.0-5.0 parts, the stearic acid is 1.0-3.0 parts, the antioxidant is 1.0-6.0 parts, the accelerator is 0.5-5 parts, and the sulfur is 1.0-10.0 parts. The application introduces a bio-based lignin branch into butyl rubber through molecular structure design, increases the internal friction between molecular chains through more active groups in the lignin macromolecule, especially the hydrogen bond effect, and further improves the hysteresis loss, the damping performance and the liquid resistance of the butyl rubber.
[0045] The high-efficiency shock-absorbing rubber pad provided by the application comprises 100.0-150.0 parts of the lignin-grafted butyl rubber, and the amount can be 100 parts, 105 parts, 110 parts, 115 parts, 120 parts, 125 parts, 130 parts, 135 parts, 140 parts, 145 parts or 150 parts.
[0046] In the application, the lignin in the lignin-grafted butyl rubber is selected from one or more of alkali lignin, dealkali lignin, sodium lignosulfonate and calcium lignosulfonate. Biomass lignin is renewable and self-sourced, and is widely used in many industrial fields due to its wide source, low price, no pollution, renewability and biodegradability. The application uses lignin-grafted butyl rubber to improve the damping and liquid resistance of butyl rubber.
[0047] The rubber pad provided by the application comprises 50-70 parts of carbon black, and the amount is specifically 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, 62 parts, 64 parts, 66 parts, 68 parts or 70 parts. In the application, the iodine adsorption value of the carbon black is 70-90 g / kg, and the oil adsorption value is 90*10 -5~128x10 -5 m 3 / kg, compression oil absorption 80x10 -5 ~95x10 -5 m 3 / kg, color strength 95~115%, CTAB adsorption specific surface area 73~85x10 3 m 2 / kg, total specific surface area 72x10 3 ~84x10 3 m 2 / kg. In specific embodiments, the carbon black is specifically carbon black N330.
[0048] The rubber pad provided by the application comprises 2.0-5.0 parts of zinc oxide, and the amount is specifically 2 parts, 3 parts, 4 parts or 5 parts.
[0049] The rubber pad provided by the application comprises 1.0-3.0 parts of stearic acid, and the amount is specifically 1 part, 1.5 parts, 2.0 parts, 2.5 parts or 3.0 parts.
[0050] The rubber pad provided by the application comprises 1.0-6.0 parts of antioxidant, and the amount is specifically 1.0 part, 1.5 parts, 2.0 parts, 2.5 parts, 3.0 parts, 3.5 parts, 4.0 parts, 4.5 parts, 5.0 parts, 5.5 parts or 6.0 parts. In the application, the antioxidant is selected from one or more of antioxidant RD, antioxidant 4020 and antioxidant NA.
[0051] The rubber pad provided by the application comprises 0.5-5 parts of accelerator, and the amount is specifically 0.5 part, 1.0 part, 1.5 part, 2.0 part, 2.5 part, 3.0 part, 3.5 part, 4.0 part, 4.5 part or 5 part. In the application, the accelerator is selected from one or more of accelerator NOBS, accelerator CZ, accelerator NS, accelerator DTDM, accelerator DM, accelerator M and accelerator TMTD.
[0052] The rubber pad provided by the application comprises 1.0-10.0 parts of sulfur, and the amount is specifically 1.0 part, 2.0 part, 3.0 part, 4.0 part, 5.0 part, 6.0 part, 7.0 part, 8.0 part, 9.0 part or 10.0 part.
[0053] As preferred, the high-damping and high-liquid-resistance rubber composition comprises the following materials: 125 parts by weight of the lignin-g-NBR, 30.0 parts by weight of carbon black, 3.0 parts by weight of zinc oxide, 1.0 part by weight of stearic acid, 2.0 parts by weight of antioxidant, 0.7 parts by weight of accelerator NS and 1.5 parts by weight of sulfur.
[0054] The application provides a preparation method of the high-damping, oil-resistant and high-efficiency damping rubber pad for compressors.
[0055] The bio-based lignin modified nitrile rubber, carbon black, zinc oxide, stearic acid and antioxidant are mixed, and then the rubber is discharged, rolled and sheeted to obtain a masterbatch;
[0056] The masterbatch, accelerator and sulfur are mixed, and then the sheeting is performed after thinning, and the high-efficiency damping rubber pad is obtained after vulcanization.
[0057] The mixing machine is used for mixing, and the rotating speed of the mixing machine is set to 70 rpm. After the lignin modified nitrile rubber is mixed in the mixing machine for 55-65 s, the carbon black, zinc oxide, stearic acid and antioxidant are mixed for 4.5-5.5 min, and then the rubber is discharged after the upper plug is cleaned and mixed for 55-65 s. After the rubber is discharged, the roll gap of the open mill is set to 6 mm, and the rubber is rolled for 4 times, and then the rubber is sheeted and stored for 4-24 h; the temperature of the open mill is set to 50 DEG C, the masterbatch is added, the rubber is wrapped around the roll for 1 min, the sulfur and accelerator are added and mixed for 2.5-3.5 min, the roll gap is adjusted to 0.2 mm, the rubber is thinned for 6 times, and then the rubber is sheeted with a roll gap of 2 mm.
[0058] The high-damping, high-damping and oil-resistant material is prepared by mixing, vulcanizing and the like of the lignin modified nitrile rubber, and the material is used for formula design to prepare the high-damping, oil-resistant and high-efficiency damping rubber pad for compressors.
[0059] In order to further illustrate the application, the bio-based lignin modified nitrile rubber and the high-damping, oil-resistant and high-efficiency damping rubber pad for compressors and the preparation method thereof are described in detail in combination with the examples, but they should not be understood as the limitation of the protection scope of the application.
[0060] Example 1
[0061] The raw material combination described in the application can be prepared according to the existing conventional technology, and the specific steps are as follows:
[0062] Reaction 1: preparation of mercapto lignin
[0063] To realize the present application, the present application first modifies the bio-based lignin, removes water from DMSO by stirring with calcium hydride overnight, and distills the dehydrated DMSO under reduced pressure. The dealkalized lignin 20 g is dried at 50°C under vacuum for 72 hours, placed in a three-neck flask after nitrogen replacement, 100 ml of dehydrated DMSO is added, and stirred vigorously. 1 g of 4-N,N-dimethylpyridine (DMAP) and 5.83 g of N,N'-dicyclohexyl carbodiimide (DCC) are added to the beaker. After the DMAP and DCC are completely dissolved, the 3-mercaptopropionic acid (3 g) solution in DMSO is slowly added through a constant pressure dropping funnel. After the addition is completed, the constant pressure dropping funnel is replaced with a condenser, and nitrogen protection is provided. The reaction is refluxed at 70°C for 72 hours. After the reaction is completed, acetone is used for sedimentation, and the filter cake is washed three times with acetone. The filter cake is dried at 40°C under vacuum for 24 hours to obtain the terminal mercapto lignin (lignin-SH-1#).
[0064] Figure 1 For the infrared spectra of the dealkalized lignin and the mercapto lignin, it can be seen from the infrared spectra that the ester group C=O double bond stretching vibration peak at 1715 cm -1 is obviously enhanced, indicating that the ester group is introduced into the dealkalized lignin; and the mercapto group stretching vibration peak at 2568 cm -1 also indicates that the terminal mercapto group is introduced into the lignin. It can be seen from Figure 1 that the mercapto lignin has been successfully prepared.
[0065] Similarly, the present application can use alkali lignin for the reaction, remove water from DMSO by stirring with calcium hydride overnight, and distill the dehydrated DMSO under reduced pressure. The alkali lignin 20 g is dried at 50°C under vacuum for 72 hours, placed in a three-neck flask after nitrogen replacement, 100 ml of dehydrated DMSO is added, and stirred vigorously. 1 g of 4-N,N-dimethylpyridine (DMAP) and 5.83 g of N,N'-dicyclohexyl carbodiimide (DCC) are added to the beaker. After the DMAP and DCC are completely dissolved, the 3-mercaptopropionic acid (3 g) solution in DMSO is slowly added through a constant pressure dropping funnel. After the addition is completed, the constant pressure dropping funnel is replaced with a condenser, and nitrogen protection is provided. The reaction is refluxed at 70°C for 72 hours. After the reaction is completed, acetone is used for sedimentation, and the filter cake is washed three times with acetone. The filter cake is dried at 40°C under vacuum for 24 hours to obtain the terminal mercapto lignin (lignin-SH-2#).
[0066] Reaction 2: Preparation of lignin grafted modified nitrile rubber
[0067] Torque rheometer set temperature 70℃, add nitrile rubber stirring at 70rps for one minute, add mercapto lignin (lignin-SH-1#) 20g and photoinitiator benzoin dimethyl ether 0.5g stirring 5 minutes, glue removal, roll temperature 50℃, roll distance 0.2mm on the roll mill to press the sheet. The rubber sheet is placed in a nitrogen glove box, using UV light source (365nm, 120W) irradiation for 3 hours, so that the Thiol-ene reaction occurs, the mercapto lignin grafted to the nitrile rubber to make lignin grafted nitrile rubber (lignin-g-NBR 1#)
[0068] Torque rheometer set temperature 70℃, add nitrile rubber stirring at 70rps for one minute, add mercapto lignin (lignin-SH-2#) 20g and photoinitiator benzoin dimethyl ether 0.5g stirring 5 minutes, glue removal, roll temperature 50℃, roll distance 0.2mm on the roll mill to press the sheet. The rubber sheet is placed in a nitrogen glove box, using UV light source (365nm, 120W) irradiation for 3 hours, so that the Thiol-ene reaction occurs, the mercapto lignin grafted to the nitrile rubber to make lignin grafted nitrile rubber (lignin-g-NBR 2#)
[0069] Torque rheometer set temperature 70℃, add nitrile rubber stirring at 70rps for one minute, add mercapto lignin (lignin-SH-1#) 20g and photoinitiator benzoin dimethyl ether 0.5g stirring 5 minutes, glue removal, roll temperature 50℃, roll distance 0.2mm on the roll mill to press the sheet. The rubber sheet is placed in a nitrogen glove box, using UV light source (365nm, 120W) irradiation for 3 hours, so that the Thiol-ene reaction occurs, the mercapto lignin grafted to the nitrile rubber to make lignin grafted nitrile rubber (lignin-g-NBR 1#)
[0070] Sample preparation:
[0071] Mixing using a small mixer, the mixer is set to 70rpm, the lignin modified nitrile rubber (lignin-g-NBR1#, lignin-g-NBR2# or lignin-g-NBR3#) prepared above or nitrile rubber (N220S) is added to the mixer and mixed for 1 minute, then carbon black N330, zinc oxide, stearic acid, antioxidant 4020, RD and other small materials are added and mixed for 5 minutes, the top plunger is cleaned and the mixing is continued for 1 minute to remove the glue. The roll distance is 6mm, and the rubber sheet is placed for 4 to 24 hours. The roll temperature is set to 50℃, the masterbatch is added, and the rubber is wrapped around the roll for 1 minute. Sulfur and accelerator are added and mixed for 3 minutes. The roll distance is adjusted to 0.2mm and the rubber sheet is wrapped for 6 times. The roll distance is set to 2mm.
[0072] To verify that the present application can improve the damping, oil resistance performance data comparison as follows:
[0073] Table 1 specific rubber group
[0074] Raw materials Comparative Example 1 Comparative Example 2 Example 1 Example 2 Example 3 N220S 100 100 0 0 0 Lignin-g-NBR 1# 0 0 120 0 0 Lignin-g-NBR 2# 0 0 0 120 0 Lignin-g-NBR 3# 0 0 0 0 125 Zinc oxide 3 3 3 3 3 Stearic acid 1 1 1 1 1 Carbon black N330 50 30 30 30 30 4020 1 1 1 1 1 RD 1 1 1 1 1 Dealkalized lignin 0 20 0 0 0 Accelerator NS 0.7 0.7 0.7 0.7 0.7 Sulfur 1.5 1.5 1.5 1.5 1.5
[0075] Table 2 physical and mechanical properties
[0076]
[0077] From Table 1 and Table 2, the tensile strength of Comparative Example 2 is lower than that of Comparative Example 1, indicating that the reinforcing effect of lignin is poorer than that of carbon black N330. The tensile strength of Example 1 and Example 3 is slightly higher than that of Comparative Example 2, indicating that this modification method can improve the tensile strength. The tensile strength of Example 1 is higher than that of Comparative Example 2, and the tan delta (25℃) and tan delta integral area are also larger, indicating that the performance of alkali lignin grafted butadiene-acrylonitrile rubber is better than that of alkali lignin grafted butadiene-acrylonitrile rubber. At the same time, it can be clearly seen from Table 2 that the liquid resistance of Example 1 and Example 3 is significantly improved, and the volume change rate is significantly reduced. The tan delta integral of Comparative Example 2 is slightly higher than that of Comparative Example 1, indicating that the use of lignin to replace part of the carbon black can improve the damping performance of the rubber, but the improvement is limited. The tan delta integral of Example 1 and Example 3 is significantly increased, indicating that after the lignin is grafted to the molecular chain of butadiene-acrylonitrile rubber, the lignin acts as a side chain of the rubber, greatly improving the damping performance of the rubber, and the more the lignin side chains, the more obvious the improvement of the damping performance. From Figure 2 It can also be seen that the tan delta integral area of Example 3 is the highest, followed by Example 1, and the damping performance is significantly better than that of Comparative Example 1 and Comparative Example 2.
[0078] From the above examples, the present application provides a bio-based lignin modified butadiene-acrylonitrile rubber, which is prepared from end thiol lignin grafted butadiene-acrylonitrile rubber. The end thiol lignin is prepared from bio-based lignin and 3-mercapto propionic acid, and the bio-based lignin is selected from one or more of alkali lignin, alkali-free lignin, sodium lignosulfonate and calcium lignosulfonate. The present application introduces biomass lignin side chains into butadiene-acrylonitrile rubber by grafting lignin onto butadiene-acrylonitrile rubber, increases the friction between molecular chains through the active groups in the lignin macromolecule, especially the hydrogen bonding, increases the internal friction, and then improves the hysteresis loss, thereby improving the damping performance and liquid resistance of butadiene-acrylonitrile rubber.
[0079] The above description is only the preferred embodiment of the present application, and it should be pointed out that for ordinary skilled in the art, without departing from the principles of the present application, a number of improvements and refinements can be made, and these improvements and refinements should also be considered as the protection scope of the present application.
Claims
1. A bio-based lignin modified nitrile rubber, prepared by grafting nitrile rubber with terminal thiol group lignin. The terminal thiol group lignin is prepared by modifying bio-based lignin and 3-mercaptopropionic acid, and the bio-based lignin is selected from one or more of alkali lignin, dealkali lignin, sodium lignosulfonate and calcium lignosulfonate. 2.A method for preparing the bio-based lignin modified nitrile rubber of claim 1, comprising the following steps: Mixing nitrile rubber, terminal thiol group lignin and photoinitiator, tabletting, reacting under ultraviolet irradiation, and obtaining lignin grafted modified nitrile rubber.
3. The production method according to claim 2, characterized by, The wavelength used for ultraviolet irradiation is 365 nm, the power is 110-130 W, and the irradiation time is 170-190 min.
4. The production method according to claim 2, characterized by, The photoinitiator is selected from one or more of 2, 2-dimethoxy-2-phenylacetophenone, benzil ketone, 2, 2'-bis (trifluoromethyl) phenyl phosphate, 2, 4, 6-trimethylphenyl phosphate, 2, 2'-bis (p-hydroxyphenyl) propane and 2, 2'-bis (p-methoxyphenyl) propane.
5. The preparation method according to claim 2, characterized in that, The terminal thiol group lignin is prepared by the following method: Mixing bio-based lignin after dehydration with dehydrated DMSO, adding esterification condensing agent, after the esterification condensing agent is completely dissolved, adding dropwise 3-mercaptopropionic acid DMSO solution, refluxing under nitrogen atmosphere to obtain terminal thiol group lignin.
6. The production method according to claim 5, wherein The esterification condensing agent is selected from one or more of 4-N, N-dimethylpyridine, N, N'-dicyclohexyl carbodiimide, carbonyl diimidazole and sulfonyl chloride.
7. The preparation method according to claim 5, characterized in that, The temperature of the refluxing reaction is 65-75℃, and the time is 70-75 h. 8.A high-damping, oil-resistant and high-efficiency shock-absorbing rubber pad for compressors, comprising the following components in mass fraction: 100.0-150.0 parts of the bio-based lignin modified nitrile rubber of claim 1, 50-70 parts of carbon black, 2.0-5.0 parts of zinc oxide, 1.0-3.0 parts of stearic acid, 1.0-6.0 parts of antioxidant, 0.5-5 parts of accelerator, and 1.0-10.0 parts of sulfur.
9. The high-damping, oil-resistant, high-efficiency shock-absorbing rubber pad for compressors according to claim 8, characterized in that, The type of the carbon black is N330. The accelerator is selected from one or more of accelerator NOBS, accelerator CZ, accelerator NS, accelerator DTDM, accelerator DM, accelerator M and accelerator TMTD. 10.A method for preparing the high-damping, oil-resistant and high-efficiency shock-absorbing rubber pad for compressors of any one of claims 8-9, comprising the following steps: Mixing the lignin modified nitrile rubber, carbon black, zinc oxide, stearic acid and antioxidant, discharging, passing through the roller, and placing the sheet to obtain the masterbatch; Mixing the masterbatch with the accelerator and sulfur, passing through the thin pass, placing the sheet, and obtaining the high-efficiency shock-absorbing rubber pad after vulcanization.
Citation Information
Patent Citations
High-damping sound-absorbing rubber and preparation method thereof
CN112094463A
Styrene-isoprene block copolymer and butyl rubber blended composition damping material
CN112175340A
Bio-based polyurethane damping material and preparation method and application thereof
CN113896859A